2019
DOI: 10.2337/db18-0796
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle–Specific Activation of Gq Signaling Maintains Glucose Homeostasis

Abstract: Skeletal muscle (SKM) insulin resistance plays a central role in the pathogenesis of type 2 diabetes. Because G-protein–coupled receptors (GPCRs) represent excellent drug targets, we hypothesized that activation of specific functional classes of SKM GPCRs might lead to improved glucose homeostasis in type 2 diabetes. At present, little is known about the in vivo metabolic roles of the various distinct GPCR signaling pathways operative in SKM. In this study, we tested the hypothesis that selective activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…By contrast, obese mice lacking Gaq/11 in SKM showed impaired glucose homeostasis [35]. Bone et al [35] also demonstrated that activation of Gqcoupled oxytocin receptors enhances glucose uptake in primary human SKM cells (Fig. 3; Table 1).…”
Section: Metabolic Functions Of Gpcrs In Skeletal Musclementioning
confidence: 97%
See 3 more Smart Citations
“…By contrast, obese mice lacking Gaq/11 in SKM showed impaired glucose homeostasis [35]. Bone et al [35] also demonstrated that activation of Gqcoupled oxytocin receptors enhances glucose uptake in primary human SKM cells (Fig. 3; Table 1).…”
Section: Metabolic Functions Of Gpcrs In Skeletal Musclementioning
confidence: 97%
“…Selective activation of this designer GPCR promoted glucose uptake into SKM and improved glucose homeostasis in diet-induced obese, glucose-intolerant mice [35]. By contrast, obese mice lacking Gaq/11 in SKM showed impaired glucose homeostasis [35]. Bone et al [35] also demonstrated that activation of Gqcoupled oxytocin receptors enhances glucose uptake in primary human SKM cells (Fig.…”
Section: Metabolic Functions Of Gpcrs In Skeletal Musclementioning
confidence: 98%
See 2 more Smart Citations
“…We recently reported that activation of Gq-coupled receptors enhanced AMPK-mediated glucose uptake in muscle [ 91 ]. Whether there is a synergistic effect between hepatic AMPK activation by metformin and Gq receptor activation in the muscle (and other tissues, including liver) is a subject to be examined.…”
Section: Gpcr Signaling In Relation To Metformin Pparγ Agonist Amentioning
confidence: 99%